A Review on Framework for Credit Outlook in Islamic Finance: a Personal Financial Perspective - Hasnol Alwee Md Salleh, Md; Abdullah, Rose; Maamor, Selamah (International Journal of Engineering and Technology, 2018)
With the development of Islamic finance since the 1970s, numerous Islamic financial concepts and products had been developed, providing the opportunity for Muslims to acquire goods and services using debt-based financing, whilst adhering to Shari’ah, notably the prohibition of riba. Islam also places significant importance towards fulfilling the rights of the creditor by repaying one’s debt and avoiding the risks of indebtedness that would harm oneself and others. Given the delicate balance between permissibility and the wary nature on credit, this study attempts to provide a framework on credit, notably in view of the contemporary financial world of today, by bringing into context the Life Cycle Hypothesis and empirical research on saving motives. Utilizing the Maqasid al-Shari’ah, the resulting framework establishes three main lines of inquiry that should be considered, prior to the attainment of credit. A preliminary discussion and recommendations is also described, emphasizing the important role of both credit and non-credit alternatives, to be considered and created by Islamic Financial Institutions.